Mobile learning : a handbook for developers, educators, and learners - McQuiggan, Scott; Kosturko, Lucy.; McQuiggan, Jaime; Sabourin, Jennifer (Hoboken, New Jersey : Wiley, 2015)
"Explore the game-changing technology that allows mobile learningto effectively reach K-12 students Mobile Learning: A Handbook for Developers, Educators andLearners provides research-based foundations for developing, evaluating, and integrating effective mobile learning pedagogy. Twenty-first century students require twenty-first centurytechnology, and mobile devices provide new and effective ways toeducate children. But with new technologies come new challenges--therefore, this handbook presents a comprehensive look at mobile learning bysynthesizing relevant theories and drawing practical conclusionsfor developers, educators, and students. Mobile devices--in ways that the laptop, the personalcomputer, and netbook computers have not--present theopportunity to make learning more engaging, interactive, andavailable in both traditional classroom settings and informallearning environments. From theory to practice, MobileLearning explores how mobile devices are different than theirtechnological predecessors, makes the case for developers, teachers, and parents to invest in the technology, and illustratesthe many ways in which it is innovative, exciting, and effective ineducating K-12 students. Explores how mobile devices can support the needs ofstudents Provides examples, screenshots, graphics, and visualizations toenhance the material presented in the book Provides developers with the background necessary to create theapps their audience requires Presents the case for mobile learning in and out of classroomsas early as preschool Discusses how mobile learning enables better educationalopportunities for the visually impaired, students with Autism, andadult learners. If you're a school administrator, teacher, app developer, orparent, this topical book provides a theoretical, well-researcheddiscussion of the pedagogical theory and mobile learning, as wellas practical advice in setting up a mobile learning strategy"--
Bridging Formal and Informal LearningConclusion; Notes; Chapter 13: Engaging Young Users: Apps for Preschoolers; Key Skills for Preschool Apps; What Makes an Engaging Preschool App?; Challenges; Conclusion; Notes; Chapter 14: Making Accessible Apps: Autism and Visual Impairment; Introduction; Advantages of the iPad for Special Populations; Autism and Autism Spectrum Disorders (ASD); Visual Impairment; Developing Accessible Apps; Conclusion; Notes; Chapter 15: Balancing Power: Data Use, Privacy, and Digital Citizenship; Privacy; Privacy Legislation; Open Issues
Machine generated contents note: Preface Acknowledgments Chapter 1: Changing Education with Mobile Learning A Brief History of Educational Technology: What willrevolutionize the system? Mobile Learning: Reaching Kids Today What is Mobile Learning? Benefits and Challenges of Mobile Learning How to Make Mobile Learning Work Conclusion Notes Section 1: The Mobile Classroom Chapter 2: The Science of Learning Introduction Information Processing and Learning Other Critical Facets of Learning Implications for Mobile Learning Conclusion Notes Chapter 3: What Is It about These Devices? Connected Aware Multimodal Familiar Personal Comprehensive Consolidated Portable Relevant Secure Conclusion Notes Chapter 4: Creating the Mobile Classroom Theoretical Foundations Instructional Methods Alternative Learning Environments Conclusion Notes Chapter 5: Higher-Order Thinking Skills and DigitalFluency Higher-Order Thinking Skills Classrooms for Higher-Order Thinking Conclusion Notes Chapter 6: Instructional Management and Levels of TechnologyAccess Mobile Learning Programs Levels of Access in the Mobile Classroom Conclusion Notes Section 2: Creating the Mobile Learning Experience Chapter 7: Mobile Technology's Defining Features Hardware Software Accessories Conclusion Notes Chapter 8: The Educational App Development Process Research Stage: Is It a Good Idea? Building the Right Team: Capturing a Variety of Expertise Building the App Case Study: App Development at SAS Curriculum Pathways Conclusion Notes Chapter 9: Design and User Experience Designing a Great App: Make It Easy Putting Great Design to Work Conclusion Notes Chapter 10: Data, Evaluation, and Learning Analytics Asking the Questions Gathering Data Mobile Data Analytics: Turning Data into Information Conclusion Notes Chapter 11: The Business of Educational Apps The Educational App Market is ... How to Sell Your App: Pricing Models How Users Buy Your App Marketing Conclusion Notes Section 3: Mobile Learning for Everyone Chapter 12: Informal Learning Developing Lifelong Learners Bridging Formal and Informal Learning Conclusion Notes Chapter 13: Engaging Young Users: Apps for Preschoolers Key Skills for Preschool Apps What Makes an Engaging Preschool App? Challenges Conclusion Notes Chapter 14: Making Accessible Apps: Autism and VisualImpairment Introduction Advantages of the iPad for Special Populations Autism and Autism Spectrum Disorders (ASD) Visual Impairment Developing Accessible Apps Conclusion Notes Chapter 15: Balancing Power: Data Use, Privacy and Digital Citizenship Privacy Conclusion Notes Chapter 16: Mobile Learning Today and Tomorrow Introduction Making Mobile Learning Work The Future Conclusion Notes Appendix A: List of Apps by Chapter Appendix B: The Great App Checklist How to Use This Checklist The Great App Checklist Notes About the Authors Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mobile communication systems in education; Educational technology; EDUCATION -- Distance Education & Learning; Educational technology; Mobile communication systems in education; Electronic books